(untitled) (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2017)
The paper covers in a synthetic way the participation and influence of the Galician in the Cuban ideology. The objective was to analyze from a historical perspective the Galician influence in the Cuban economy. The methodology used was the realization of a retrospective and transversal analysis of the Galician influence in the economic and social life of Cuba. Both the stated objective and the methodology, together with other research techniques allow us to propose as main results, that the Galician presence reached almost all branches of industry and services of Cuban social and economic life, with a prominent participation in the tobacco and services sectors (small wineries or supplies sold to the population). It shows some of the exponents of the tobacco sector and how many of them came to transform this industry, of the winemakers are detailed how they knew how to socialize with their charismatic character in the areas where they settled. It is detailed how the Galician after obtaining a fortune was affected by the measures adopted by the revolutionary government. Finally, it is concluded that it is difficult to write the economic, political and social history of Cuba without it not being immersed a Galician.